Efficacy of Novel Schiff base Derivatives as Antifungal Compounds in Combination with Approved Drugs Against Candida Albicans - Malik, Manzoor A.; Lone, Shabir Ahmad; Gull, Parveez; Dar, Ovas Ahmad; Wani, Mohmmad Younus; Ahmad, Aijaz; Hashmi, Athar Adil (Medicinal Chemistry, 2019)
Background: The increasing incidence of fungal infections, especially caused by Candida albicans, and their increasing drug resistance has drastically increased in recent years. Therefore, not only new drugs but also alternative treatment strategies are promptly required. Methods: We previously reported on the synergistic interaction of some azole and non-azole compounds with fluconazole for combination antifungal therapy. In this study, we synthesized some non-azole Schiff-base derivatives and evaluated their antifungal activity profile alone and in combination with the most commonly used antifungal drugs- fluconazole (FLC) and amphotericin B (AmB) against four drug susceptible, three FLC resistant and three AmB resistant clinically isolated Candida albicans strains. To further analyze the mechanism of antifungal action of these compounds, we quantified total sterol contents in FLC-susceptible and resistant C. albicans isolates. Results: A pyrimidine ring-containing derivative SB5 showed the most potent antifungal activity against all the tested strains. After combining these compounds with FLC and AmB, 76% combinations were either synergistic or additive while as the rest of the combinations were indifferent. Interestingly, none of the combinations was antagonistic, either with FLC or AmB. Results interpreted from fractional inhibitory concentration index (FICI) and isobolograms revealed 4-10-fold reduction in MIC values for synergistic combinations. These compounds also inhibit ergosterol biosynthesis in a concentration-dependent manner, supported by the results from docking studies. Conclusion: The results of the studies conducted advocate the potential of these compounds as new antifungal drugs. However, further studies are required to understand the other mechanisms and in vivo efficacy and toxicity of these compounds.
Keywords: Schiff base compounds